Rozwiązane

Oblicz wartość wyrażenia
( − 3)( + 3) + ( + 2)( − 2) − ( + 3)( − 3) dla = √3 − 1



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

√ -- √ -- 4− 2 3 > 4 − 2 4 = 0,  

więc

∘ (------√--)2- ∘ |-----√--| ∘ -----√--- 4 4− 2 3 = 2 ||4− 2 3|| = 24 − 2 3 .  

Zauważmy teraz, że wyrażenie pod pierwiastkiem to pełen kwadrat

∘ --------- ∘ ------------- ∘ ----------- -- -- 4 − 2√ 3 = 3− 2√ 3 + 1 = (√ 3− 1)2 = |√ 3− 1 | = √ 3− 1.  

 

Odpowiedź:  -- √ 3 − 1 ]

Odpowiedź:

( − 3)( + 3) + ( + 2)( − 2) − ( + 3)( − 3) = -9 - 4 + 9 = -4

dla = √3 − 1  ?   dla? dla jakiej niewiadomej?

Szczegółowe wyjaśnienie: